THE CORRELATION BETWEEN STUDENTS’ WRITING ATTITUDE AND COMPOSITION PERFORMANCE - Wagiyo, Supiah (Scientia: Jurnal Hasil Penelitian, 2021)
The main objectives of this study were to find out (1) whether student’ writing attitude correlates with their composition performance (2) whether the factors of writing attitude correlate with their composition performance, (3) whether students’ writing attitude give contribution to the value of their writing composition and (4) whether the factors of students’ writing attitude give contribution to their composition performance. The population and sample of the study covered one hundred and fifty-six students of six semester of English Study Program. The data were obtained giving a questionnaire and composition writing test. The data collected from were analyzed by using regression analysis and hypothesizes were tested by using F-test. The results show that there were significant correlation between the student writing attitude (total) and their composition performance. (R =.242 and R²=.058). Out of the five factors of student writing attitude, there were three factors which had a significant statistical relationship with the student composition performance. They were writing perception (R= .220 and R²= .049), positive writing activities (R= .176 and R²=.031), and reading preferences (R= .193 and R²= .037). The first factor, writing perception give much contribution to the sub scales of composition performance. Furthermore, the unhypothesized findings showed that gender and writing attitude were correlated significantly in composition performance since the mean value was balanced between male and female students. However, based on the mean value, male group has better writing attitude while female group has better composition performance. Finally, the results of this research are hopefully beneficial for the English teaching and learning processes, such as writing skills. Student’s writing attitude should be considered since students may have different attitude toward writing that can affect their performance in writing.